Konsep Pendidikan Dalam Pemikiran Ki Hajar Dewantara dan Relevansinya Terhadap Pendidikan Di Indonesia - Ikhwan Aziz Q; Subandi Subandi; Retno Firmawati Nafi'ah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study focuses on the concept of education by Ki Hajar Dewantara and its relevance to education in Indonesia. The purpose of this research theoretically, can contribute to developing the concept of education in Indonesia and benefit all Indonesian people, especially in developing insight into the knowledge and thinking patterns of educators. This research is a qualitative research with a type of library research that is exploring the ideas of Ki Hajar Dewantara about education. Data collection techniques by collecting books, journals and others related to discussion. Data that has been collected is analyzed using descriptive methods, namely research methods that attempt to reveal the facts of an event, object, activity, process, and human beings as they are at the present time or the time period that is still possible in the memory of the respondent. The results of this study indicate that the concept of Ki Hajar's education is still relevant today. Judging from his thoughts in accordance with the concepts that are still being implemented, namely education and teaching which is a deliberate effort to liberate the physical and inner aspects of the human being.